Grape peel powder promotes intestinal barrier homeostasis in acute TNBS-colitis: A major role for dietary fiber and fiber-bound polyphenols. (September 2019) - Maurer, Luana Haselein; Cazarin, Cinthia Baú Betim; Quatrin, Andréia; Minuzzi, Natália Machado; Costa, Eduarda Lasch; Morari, Joseane; Velloso, Lício Augusto; Leal, Raquel Franco; Rodrigues, Eliseu; Bochi, Vivian Caetano; Júnior, Mário Roberto Maróstica; Emanuelli, Tatiana
Abstract: Inflammatory bowel diseases are characterized by impaired intestinal barrier function. This study aimed to evaluate the effects of grape peel powder (GPP) and its bioactive rich-fractions on the barrier function and colonic injury in a model of colitis induced by 2, 4, 6 trinitrobenzene sulfonic acid (TNBS). Wistar rats received diets supplemented with either GPP (8%), extractable polyphenols (EP), non-extractable polyphenols-rich fraction (NEP-F), or polyphenols-poor, fiber-rich fraction (F) from grapes at amounts equivalent to the GPP group during 15 days before and for 7 days after colitis induction. NEP-F has decreased the extension of colonic lesion but the other grape peel bioactive fractions did not protect against macroscopic or microscopic colonic damage, EP diet increased macroscopic colonic damage. GPP, EP, and NEP-F reduced claudin-2 mRNA expression, whereas GPP and F fraction increased occludin and ZO-1 mRNA expression. All experimental diets reduced the colitis-triggered increase of MMP-9 mRNA expression. Colitis reduced by 30% the production of cecal short-chain fatty acids (SCFA). GPP and NEP-F completely protected against this effect, whereas F fraction was ineffective. Only GPP and NEP-F were able to decrease the upregulation of GRP94 mRNA triggered by colitis. Dietary fiber seems to reestablish the intestinal barrier function, whereas fiber-bound phenolics were able to restore cecal metabolism to produce beneficial metabolites like SCFA and to reduce the activation of the unfolded protein response. Graphical abstract: Unlabelled Image Highlights: Extractable polyphenols (EP) from grape peel worsened TNBS-induced colonic damage. Fraction rich in non-extractable polyphenols and fiber (NEP-F) had protective effects. NEP-F was as effective as mesalamine to decrease the area of colonic lesion. Fiber-rich fraction (F) of grape peel improved the colonic barrier permeability. NEP-F but not F fraction enhanced the cecal production of short chain fatty acids.